Identifying components existing in Agile software development for achieving “light but sufficient” documentation - Basit Habib; Rohaida Romli; Malina Zulkifli (Journal of Engineering and Applied Science, 2023)
Abstract The Agile nature allows changes within the development procedure which can sometimes be non-predictable and affect the cost and time of the software. Face-to-face communication appears to be a faster process in Agile Software Development (ASD) in practice, but issues such as understandability and communicativeness cause ambiguity between the customer and the developer. Among the existing works, achieving light but sufficient documentation in ASD remains a challenge. Most previous studies have simply highlighted the issues associated with less documentation, its limitations, and challenges, but no proper solution has yet been proposed. As an initial step in our theoretical study, we conducted a systematic literature review (SLR) to identify the related components and subcomponents that are applicable in supporting Agile documentation. As such, the fundamental concepts related to software documentation have been studied in order to align with documentation in ASD. The identification of these components can be useful in achieving the concept of “light but sufficient” documentation in Agile, which will aid in achieving customer satisfaction.